According transformer parameters to design a high voltage power. Issue 1 (1st November 2022) - Zhang, Junling; Jin, Renbo
Abstract: When the load is empty pulse width modulation high frequency and high voltage power' stabilization depth can easily cause oscillation, and when the full load of the voltage regulation is too shallow the voltage regulation effect is not good, the reason for this phenomenon is because the equivalent ratio and load correlation. The first thing you need to do is to find out why you can avoid the problem early in the design. To find out the cause, should to know the influence of the high voltage rectifier circuit on the total gain of the circuit and the dispersed parameters of the high frequency and high voltage transformer.